(untitled) (Vietnam Journal of Community Medicine, 2022)
Background: The acute respiratory infection caused by the SARS-CoV-2 virus has become a global pandemic. Faced with the nature and complexity of the epidemic, many governments have enacted social distancing and isolation measures. These measures cause significant changes in an individual’s functioning, including sexual functioning and functioning. Aim: Evaluation of the impact of the Covid-19 epidemic on male sexual activity and male sexual function. Methods: Two hundred and seventy men completed a set of telephone interview questionnaires. Evaluation of sexual activity and function through collecting and analyzing variables on the frequency of sexual activity, level of Satisfied sex life, IIEF-5 scale, PEDT, IELT time, orgasm level. Results: Sexual activity: The frequency of sexual intercourse, the frequency of masturbation before - during the epidemic was 2.7 ± 0.14 and 2.35 ± 0.18 times/week, respectively (p<0.001); 2.42 ± 0.29 and 2.52 ± 0.39 times/week (p=0.462). The sexual satisfaction scores before - during the epidemic were 4.6 ± 0.07 and 4.39 ± 0.45 points (p < 0.005). Sexual function: 79.3% did not change libido before and during the epidemic. Comparison before and during the epidemic: the rate of erectile dysfunction is 14.03% and 14.5%, respectively; premature ejaculation was 21.27% and 22.5%, IIEF-5 score was 23.12 ± 0.36 and 23.02 ± 0.44 points (p=0.936), PEDT score was 7.62 ± 0, 55 and 7.85 ± 0.59 points (p = 0.806), IELT time was 8.35 ± 0.89 and 8.57 ± 1.01 min (p = 0.120). Conclusion: The frequency of sex and the level of sexual satisfaction during the epidemic decreased compared to before the epidemic Covid-19. There is no significant difference between the incidence of erectile dysfunction, premature ejaculation, the IIEF-5 score, the PEDT, and the IELT time before and during the epidemic Covid-19.